Immunohistochemical expression of P53 and Ki-67 on epithelial tumors of ovary - Mohapatra, Ipsita; Harshini, Nikku; Samantaray, Subha Ranjan; Sahitya, K. Anantha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ovarian cancer is the third most common gynaecologic cancer and it is well known for its late presentation at advanced stage. Epithelial tumors of the ovary (EOT) are commonest of all ovarian neoplasms and their malignant forms represent about 90% of ovarian cancers. The determination of cell proliferation has been reported to be of diagnostic and prognostic significance. Over expression of p53 and Ki-67 has been claimed to be a marker of poor prognosis in epithelial ovarian tumors. Aim this study was to evaluate the biological significance of p53 and Ki-67 and their antigen expression in epithelial ovarian cancer. Methods: This is an observational study of 52 cases of ovarian tumors which were diagnosed and operated at Dept of Gynaecology, Prathima institute of medical sciences in South India, between August 2018 to July 2020. Results: The mean age of diagnosis for benign, borderline and malignant epithelial tumors was 42years, 49 years, 56years respectively. Most common histological type was serous epithelial tumors (50%). Highest p53 and Ki-67 immunoreactivity was seen in malignant tumors. Their co-expression was seen in 46.2% of the cases. Conclusions: Epithelial tumors and their malignant forms are common ovarian cancers, which are well known for its lethality and late presentation. Immunohistochemical markers p53 and Ki-67 frequently over expressed in epithelial tumors and has a prognostic role in determining the biologic tumor behaviour which further helps in planning the treatment.